Performance evaluation of concatenate coding for body area network applications - Sansoda, Buncha; Choomchuay, Somsak (My University, 2014)
In digital communications, since it is of importance that the receiving data is identical to the transmitted data, the error correcting code is one good solution to maintaining the information accuracy between the transmitter and the receiver. This research paper proposes the application of the error correcting code to Wireless Body Area Network (WBAN). The error correcting code in this research work is the concatenate code of the Reed-Solomon code (RS) and the convolutional code (CC). Information data in WBAN with the Rician channel condition is modulated with the Binary Phase Shift Keying (BPSK) scheme. In addition, the path loss of WBAN is examined. The Additive White Gaussian Noise (AWGN) and Rayleigh fading channels are employed for comparison purposes to illustrate the effects on bit error performance of different channel environments. The RS code is an outer code while the convolutional code an inner code. The findings show that the concatenate code performs better than the single codes, i.e. RS and CC. At BER 10-3, the concatenate code {RS(255,223)+CC(171,133)} is better than either RS(255,223) at 5dB or CC(171,133) at 1.5dB. If the inner code is changed to CC(7,5) at BER 10-3, the performance is reduced by approximately 0.6dB. Thus, the coding complexity can be tailored according to the desired error correcting capability. © (2014) Trans Tech Publications, Switzerland.
Keywords: Body area network; Concatenate; Convolutional; Reed-solomon